2013
DOI: 10.1007/s00170-013-5408-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of applicability of a picosecond laser for micro-polishing of micromilled Inconel 718 superalloy

Abstract: /npsi/ctrl?action=rtdoc&an=21270450&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21270450&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Corresponding experimental validation trials carried out at pulse durations of 300 and 650 ns, reduced the average workpiece surface roughness Ra to 66 and 47 nm respectively, from an initial value of 95-96 nm. Hafiz et al [27] evaluated the feasibility of using a picosecond laser for micropolishing of Inconel 718 and in particular the effects of laser fluence/energy density. Ablation and melting regimes were prevalent when operating at fluence levels of 0.19-0.24 J/cm 2 and 0.13-0.18 J/cm 2 respectively.…”
Section: Laser Polishing Of Nickel and Titanium Alloysmentioning
confidence: 99%
“…Corresponding experimental validation trials carried out at pulse durations of 300 and 650 ns, reduced the average workpiece surface roughness Ra to 66 and 47 nm respectively, from an initial value of 95-96 nm. Hafiz et al [27] evaluated the feasibility of using a picosecond laser for micropolishing of Inconel 718 and in particular the effects of laser fluence/energy density. Ablation and melting regimes were prevalent when operating at fluence levels of 0.19-0.24 J/cm 2 and 0.13-0.18 J/cm 2 respectively.…”
Section: Laser Polishing Of Nickel and Titanium Alloysmentioning
confidence: 99%
“…Much of the later LP research focussed on ferrous materials, predominantly involving tool steels [8,9], although several carbon [10] and stainless steel grades [11] have also been investigated. Similarly, the process has been successfully employed for improving the surface morphologies of components made from nickel [12] and titanium [13] alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was recently reported that continuous surface melting can even be realized by fs lasers (or ps lasers in more studies) through heat accumulation via MHz-level pulse repetition rates [43][44][45][46]. Such a fs-laser-induced continuous surface melting process could also benefit the achievement of extremely low surface roughness for AM parts.…”
Section: Optimization Of Grazing-incidence Fs Laser Polishing For Min...mentioning
confidence: 99%